OPTIMALISASI FUNGSI DINAS PERHUBUNGAN KABUPATEN TANGERANG DALAM PROSES REKOMENDASI PEMBANGUNAN HELIPORT - Togi Sinaga; Rudy Rudy; Elfi Amir; Endang Sugih Arti; Rini Sadiatmi (Darmabakti: Jurnal Inovasi Pengabdian dalam Penerbangan, 2021)
The phenomenon of the development of heliport construction in Greater Tangerang is an opportunity for the local government and is part of one of the functions of the Department of Transportation that needs to be optimized, through Community Service activities this time the Diploma III Study Program of Aeronautical Information at the Indonesian Aviation Polytechnic Curug held a sharing session regarding the importance of understanding technical matters. and administrative related to heliport construction recommendations. The purpose of this activity is a sharing session with officials and personnel of the Tangerang Regency Transportation Service regarding the heliport development process between the local government authorities and the regulators who are responsible for the technical aspects of flight safety. The method of activity is socialization and sharing of joint policies regarding heliport development. The Director-General of Civil Aviation is a technical partner related to aviation safety aspects that need to have collaborated with local government authorities related to areas and Building Construction Permits (IMB). Clarity about the recommendation process for heliport development in an area will encourage investors or development initiators which of course are expected to have a direct or indirect impact on the development and welfare of the local community.